Possible errors in electrochemical detection of blood glucose - Badea, Mihaela; Pascu, Alina Mihaela; Nicolae, Ramona Alexandra; Taus, Nicoleta; Nunes, Gilvanda Silva; Moga, Marius Alexandru (Univerzita Pardubice, 2014)
The need of dosage of glucose concentration required to develop test methods that allow rapid and accessible even at home. It is necessary to follow a simple protocol that minimizes errors and interferences using some functions of these devices. We have identified possible errors in obtaining experimental data: lower sample volume, consume of different foods in the evening and the morning of blood collection, type of sample analysed (serum/plasma, venous/capillary blood). The data obtained using commercial biosensors were compared with spectrometric methods and good report was obtained.
Keywords: blood glucose; electrochemical detection